HOMOEOPATHIC MANAGEMENT IN THE TREATMENT OF PSORIASIS – A CASE SERIES - DR ASHA PRIYANKA; DR JAYASHREE.P; DR SANGAMESH; DR. PRAVEEN KUMAR PD.; DR VEERABHADRAPPA C (The Bioscan, 2026)
Psoriasis is a chronic inflammatory skin condition characterized by recurrent episodes of erythematous, scaly plaques; it is often associated with physical and psychological stress with impaired quality of life. Homeopathy represents psoriasis as an external expression of internal constitutional and miasmatic disturbance, requiring an individualized therapeutic approach rather than symptomatic suppression. This case series includes three patients clinically diagnosed with psoriasis successfully managed with individualized homeopathic medicines after detailed case taking. The prescribed remedies were Phosphorus, Arsenicum Iodum and Aurum Metallicum. Remedies were prescribed according to the totality of symptoms and administered according to homeopathic principles, follow ups were done over a definite period of time and outcomes were evaluated based on lesion improvement, symptom reduction, relapse frequency and overall sense of wellbeing. All cases showed sustained improvement with notable reduction in lesions, itching and scaling which was calculated using PASI score. No adverse effects or disease suppression was recorded. The findings suggests that individualized homeopathic treatment may be effective in the management of psoriasis. Further controlled and long-term studies are required to substantiate these findings.